DPV and SWV Determination of Estrone Using a Cathodically Pretreated Boron‐Doped Diamond Electrode. Issue 7 (11th June 2014) - Brocenschi, Ricardo F.; Rocha‐Filho, Romeu C.; Biaggio, Sonia R.; Bocchi, Nerilso
Abstract Voltammetric methods for estrone determination were developed using a cathodically pretreated BDD electrode with DPV or SWV. Analytical curves were obtained for estrone concentrations from 0.20 or 0.10 to 2.0 µmol L−1, for DPV or SWV, with detection limits of 0.20 and 0.10 µmol L−1, respectively. The SWV method was successfully applied in estrone recovery studies in different water matrices. Additionally, these recovery results were reasonably similar to those attained using HPLC/UV‐vis. Comparatively to other electroanalytical methods based on different carbon electrodes, the here‐reported novel methods yield very good results, being adequate for estrone determination in environmental samples.